PENGARUH SURPLUS FREE CASH FLOW DAN MEKANISME GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - S. Willy Rahadyan W; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
The aim of this research is to investigate the influence of surplus free cash flow and good corporate governance mechanisms to earning management. Good corporate governance mechanisms that used in this research, such as : board of commissioner size, board of commissioner independent, audit committee size, the frequency of audit committee meetings, and the number of finance experts audit committee.The sample in this research are manufacturing companies which were listed in Indonesia Stock Exchange.in the year of 2012-2013. Total sample in this research are 139 companies that selected with purposive sampling method. This research uses multiple regression analysis method to investigate the influence of surplus free cash flow and good corporate governance mechanisms to earning management.The results of this research indicate that surplus free cash flow had a positive significant influence to earning management, board size had a negative significant influence to earning management. Board of commissioner independent, audit committee size, the frequency of audit committee meetings, and the number of finance experts audit committee had not a significant influence to earning management.